Integrated quantum photonics - Bonneau, D; Kalasuwan, P; Laing, A; Lawson, T; Matthews, J; Peruzzo, A; Poulios, K; Shadbolt, P; Hadden, J; Harrison, J; Stanley-Clark, A; Marseglia, L; et al. (2010)
We describe our developments in integrated quantum photonics, including waveguide circuits to implement quantum logic operations, quantum metrology and quantum walks. © 2010 OSA /FiO/LS 2010.